Effects of Eco-Design, Biospheric Values, Green Management and Green Reputation on the Perceived Green Performance of Airport Facilities and Services - Bamidele, Ruth Oluyemi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The energy-intensive international airport operations represent a critical component of the tourism industry in any economy. Achieving and improving the green performance of airport facilities and services through green practices at international airports is more crucial than ever before due to the positive impact on tourism demand, destination image, economic benefit, social responsibility, cleaner environment, and the overall implications for sustainable tourism development. Hence, it is pertinent to investigate factors that influence green behavior among airport employees and management and their perception of the green performance of airport facilities and services. The essence of this study is to understand how stakeholders’ behavior and perception of the eco-design of airport buildings with other sustainable practices can improve green performance at international airports’ operations and boost sustainable tourism development at destinations. Using the Extended Theory of Planned Behavior (E-TPB) and Triple Bottom Line (TBL)/Sustainable Economic Development Theory (SED) (TBL/SED), PLS-SEM, bootstrapping, and Importance-Performance Map Analysis (IPMA) for statistical analysis, this dissertation investigates the effects of eco-design, biospheric values, green management and green reputation on the perceived green performance of airport facilities and services. A two time-lag design with two weeks intervals was used for the multisource-data collection from employees at Nigeria's Lagos and Abuja international airports. iv Findings reveal that, first, the biospheric value (BV) of individuals is one of the most crucial factors in influencing pro-environmental behavior among airport employees, which in turn is analogous to improvement in the green performance of the airports. BV also promotes the ability of employees to recognize sustainable practices at the airports, which is critical for destination image and tourist demand. Second, the findings indicate distinct differences in the total effects (importance) and groupspecific performance of some of the constructs, such as biospheric values, green airport reputation, eco-design of the airport, and perceived green performance in this crosssectional study. Theoretical and practical implications and contributions of the study, limitations, and recommendations for future research in line with the findings are also given.

ÖZ: Enerji yoğun uluslararası havalimanı operasyonları, herhangi bir ekonomide turizm endüstrisinin kritik bir bileşenini temsil eder. Turizm talebi, destinasyon imajı, ekonomik fayda, sosyal sorumluluk, daha temiz çevre ve sürdürülebilir turizm gelişimi için genel etkiler üzerindeki olumlu etki nedeniyle, uluslararası havalimanlarındaki yeşil uygulamalar yoluyla havalimanı tesislerinin ve hizmetlerinin yeşil performansının elde edilmesi ve iyileştirilmesi her zamankinden daha önemlidir. Bu nedenle, havalimanı çalışanları ve yönetimi arasındaki yeşil davranışı ve havalimanı tesis ve hizmetlerinin yeşil performansına ilişkin algılarını etkileyen faktörlerin araştırması gerekmektedir. Bu çalışmanın özü, paydaşların diğer sürdürülebilir uygulamalarla birlikte havalimanı binalarının eko-tasarımına yönelik davranışlarının ve algılarının uluslararası havalimanlarının operasyonlarında yeşil performansı nasıl iyileştirebileceğini ve destinasyonlarda sürdürülebilir turizm gelişimini nasıl destekleyebileceğini anlamaktır. Bu tez, istatistiksel analiz için Genişletilmiş Planlı Davranış Teorisi (E-TPB) ve Üçlü Alt Sınır (Bilanço) (TBL)/Sürdürülebilir Ekonomik Kalkınma Teorisi (SED) (TBL/SED), PLS-SEM, önyükleme ve önem-performans matrisi analizini (IPMA) kullanarak havalimanı tesisleri ve hizmetlerinin algılanan yeşil performansı üzerinde çevre tasarımı, biyosferik değerler, yeşil yönetim ve yeşil itibarın etkilerini araştırmaktadır. Nijerya'nın Lagos ve Abuja uluslararası havalimanlarındaki çalışanlardan çok kaynaklı veri toplamak için iki haftalık aralıklarla iki zaman gecikmeli bir tasarım kullanılmıştır. vi Bulgular, ilk olarak, bireylerin biyosferik değerinin (BV), havalimanlarının yeşil performansındaki iyileşmeye benzer şekilde, havalimanı çalışanları arasında çevre yanlısı davranışı etkilemede en önemli faktörlerden biri olduğunu ortaya koymaktadır. BV ayrıca çalışanların, destinasyon imajı ve turist talebi için kritik olan havalimanlarındaki sürdürülebilir uygulamaları tanıma becerisini de desteklemektedir. İkinci olarak, bu kesitsel çalışmanın bulguları biyosferik değerler, yeşil havaalanı itibarı, havaalanının eko-tasarımı ve algılanan yeşil performans gibi bazı yapıların toplam etkilerinde (öneminde) ve gruba özgü performansında belirgin farklılıklar olduğunu göstermektedir. Çalışmanın teorik ve pratik çıkarımları ve katkıları, sınırlılıkları ve bulgular doğrultusunda gelecek araştırmalar için öneriler de verilmektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2023. Co-Supervisor: Assoc. Prof. Dr. Mine Haktanır and Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Tourism Faculty; Tourism--Sustainable Tourism--Green Tourism; Tourism--Airport Facilities--Airport Management--Green Performance; Eco-design of airport buildings; green management intransigence; perceived green performance; biospheric value; green airport reputation; sustainable tourism